Structural Imbalances and their impact on Sectoral Growth and Employment in Iraqi Economy for the period 2003-2015: Analytical study. - صالح, لورنس يحيى; نوري, محمد طاهر (Journal of Economics and Administrative Sciences, 2018)
Abstract:     The objective of this study, is to attempt to explain the reality of the Structural Imbalances in the Iraqi Economy during the period of research, by providing a quantitative analysis of the most important types of Imbalances, Which are represented by the disruption in the Productive Structure, the imbalance of the structure of Public Budget, and the imbalance of the Structure of Trade. The problem of the research, is the fact that the economy structure in Iraq has long suffered from an Imbalances in its economic structure, which are represented in the unequal relations between its constituent elements, according to the proportions levels defined by the economic theory. This has resulted in a weak growth in the sectoral contribution to GDP, and employment and the continued profitability of the economy based on oil exports. Hence the importance of research, is an attempt to study and analyze the most important manifestations of these imbalances, through the use of quantitative indicators and relative proportions. The study concluded that there are obvious Structural Imbalances, the most prominent of these are the imbalance of the public expenditure structure, which is the lack of proper proportion between its investment and operational naps, as well as the imbalance of the structure of public revenues, which is highly dependent on oil rents. And all of this has led to imbalance in the structure of foreign trade of the country represented in increasing the degree of commercial exposure due to the growth of imports and its superiority over exports, if we excluded oil. The result of all this was the faltering and weak development process, which negatively affected the reality of economic operation. The researcher recommends, to supporting the sectoral productive growth in agriculture, industry, and services, especially tourism of all kinds. This is done only creating harmony between financial, monetary and trade policies, as well as supporting the role of the private sector and encouraging the foreign investment.